Total synthesis of the endogenous inflammation resolving lipid resolvin D2 using a common lynchpin - Li, John; Leong, May May; Stewart, Alastair; Rizzacasa, Mark A. (Beilstein Journal of Organic Chemistry, 2013)
The total synthesis of the endogenous inflammation resolving eicosanoid resolvin D2 (1) is described. The key steps involved a Wittig reaction between aldehyde 5 and the ylide derived from phosphonium salt 6 to give enyne 17 and condensation of the same ylide with aldehyde 7 to afford enyne 11. Desilylation of 11 followed by hydrozirconation and iodination gave the vinyl iodide 4 and Sonogashira coupling between this compound and enyne 3 provided alkyne 18. Acetonide deprotection, partial reduction and ester hydrolysis then gave resolvin D2 (1).
Keywords: catalysis; eicosanoid; natural product; resolvin D2; Sonogashira coupling; total synthesis; Wittig reaction